2013
DOI: 10.1177/1756287213490052
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravesical sodium hyaluronate/chondroitin sulfate therapy for interstitial cystitis/bladder pain syndrome: a prospective study

Abstract: Despite the limitations of this study, the outcomes confirmed the role of combination therapy with HA and CS as a safe and effective option for the treatment of IC/BPS. Further randomized controlled studies with a higher number of patients and a longer follow-up period are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…The following data were extracted from each of the eligible studies [16][17][18][19][20][21][22][23][24][25]: the first author's name, year of publication, number of patients, patients' ages, products used, instillation regimens, visual analogue scale related pain symptom (VAS), total scores of the O'Leary-Sant Interstitial Cystitis Symptom Index (ICSI) and Problem Index (ICPI), storage symptoms such as frequency and nocturia, bladder volume, and voided urine volume. Any disagreements were resolved by consensus.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following data were extracted from each of the eligible studies [16][17][18][19][20][21][22][23][24][25]: the first author's name, year of publication, number of patients, patients' ages, products used, instillation regimens, visual analogue scale related pain symptom (VAS), total scores of the O'Leary-Sant Interstitial Cystitis Symptom Index (ICSI) and Problem Index (ICPI), storage symptoms such as frequency and nocturia, bladder volume, and voided urine volume. Any disagreements were resolved by consensus.…”
Section: Data Extractionmentioning
confidence: 99%
“…Steinhoff et al found a 45% response rate after initial 3 months with instillation of 40 ml CS 0.2%, and Nickel et al reported that instillation of CS 2% produced a 60% response rate at 6 months [27,29]. Furthermore, several studies also reported a significant effect with the combination of HA and CS, Porru et al assumed that HA/CS may give better longer-lasting therapeutic effects than the individual compounds [17,23,30]. In the present study, although mean difference of VAS in the pure HA subgroup was higher than that in the subgroup with combination of HA and CS, there was no significant difference between subgroups (P = 0.722).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Porru et al [21], Cervigni et al [52], and Giberti et al [53] used an intravesical injection of 1.6 % hyaluronic acid and 2.0 % chondroitin sulfate as a treatment for BPS/IC, and observed a decrease of 35-50.76 % in pain, a decrease of 26-57.14 % in voiding frequency, and an increase of 24.90-41 % in voided volume [21; 52]. The study had many limitations; however, they reported an improvement in BPS/ IC symptoms [53].…”
Section: Hyaluronic Acid+chondroitin Sulfatementioning
confidence: 98%
“…11 Sodium hyaluronate and chondroitin sulfate (iAluRil) -Giberti et al reported a statistically significant improvement in interstitial cystitis symptom index score (ICSI) post-treatment in 20 patients treated with this combination therapy. 12 Alkalinised lignocaine (with bicarbonate) -A randomised controlled trial of 102 patients by Nickel et al reported 30% of patients experienced significant improvement in their symptoms after completing a five-day course of treatment. 13 Lignocaine, heparin and sodium bicarbonate (Parson's 'cocktail') -The combination of these three instillations into the bladder reduces the nerve sensitivity of the bladder and helps to repair the lining of the urothelium.…”
Section: Bladder Instillationsmentioning
confidence: 99%